Determination of azithromycin in raw materials and pharmaceutical formulations by HPLC coupled with an evaporative light scattering detector - Aiguo Zeng; Xia Liu; Siruo Zhang; Yan Zheng; Ping Huang; Kangli Du; Qiang Fu (Elsevier, 2014)
A simple high-performance liquid chromatography (HPLC) method coupled with an evaporative light scattering detector (ELSD) was developed for the determination of azithromycin in raw materials and pharmaceutical formulations (injections, capsules and tablets) without any pretreatment or derivatization step. Azithromycin, degradation products and formulation ingredients were separated efficiently by using the mobile phase consisted of ammonium acetate (0.05 M, pH 8.0) and acetonitrile (60:40, v/v) in an isocratic mode at 0.8 ml/min flow rate. Parameters of ELSD were 60 °C for evaporation temperature and 50 psi for pressure of carrier gas (air). A logarithmic calibration curve was obtained from 50.93 to 509.30 μg/ml (r = 0.9996) for azithromycin, with the limit of detection (LOD) of 6.75 μg/ml (S/n = 3) and the limit of quantification of 22.50 μg/ml (S/n = 10). The developed method was validated and applied with satisfactory accuracy and precision for the determination of azithromycin in raw materials and pharmaceutical formulations (recovery 99-102%, RSD <1.2%, n = 3). No significant difference (t-test) was found between the results of the developed HPLC-ELSD method and the HPLC-UV or microbiological method.